Time course of the hemoglobin mass response to natural altitude training in elite endurance cyclists - Garvican, L.; Martin, D.; Quod, M.; Stephens, B.; Sassi, A.; Gore, C. (Scandinavian Journal of Medicine & Science in Sports, 2012)
To determine the time course of hemoglobin mass (Hbmass) to natural altitude training, Hbmass, erythropoietin [EPO], reticulocytes, ferritin and soluble transferrin receptor (sTfR) were measured in 13 elite cyclists during, and 10 days after, 3 weeks of sea level (n=5) or altitude (n=8, 2760 m) training. Mean Hbmass, with a typical error of ?2%, increased during the first 11 days at altitude (mean ± standard deviation 2.9 ± 2.0%) and was 3.5 ± 2.5% higher than baseline after 19 days. [EPO] increased 64.2 ± 18.8% after 2 nights at altitude but was not different from baseline after 12 nights. Hbmass and [EPO] did not increase in sea level. Reticulocytes (%) were slightly elevated in altitude at Days 5 and 12 (18.9 ± 17.7% and 20.4 ± 25.3%), sTfR was elevated at Day 12 (18.9 ± 15.0%), but both returned to baseline by Day 20. Hbmass and [EPO] decreased on descent to sea level while ferritin increased. The mean increase in Hbmass observed after 11 days (?300 h) of altitude training was beyond the measurement error and consitent with the mean increase after 300 h of simulated live high:train low altitude. Our results suggest that in elite cyclists, Hbmass increases progressively with 3 weeks of natural altitude exposure, with greater increases expected as exposure persists.